Peranan Ketrampilan dan Kemampuan Staff Pastry Dalam Menjaga Kualitas Produk di Aston Kupang Hotel & Convention Center - Zakharia, Friend (Jurnal Ilmiah Global Education, 2025)
The pastry department in a hotel is very important, especially in creating quality cake or bread products. Various industries are developing and improving to maintain quality, one of which is the Aston Kupang Hotel and Convention Center. This research is qualitative descriptive using data collection methods through observation, interviews, and documentation. The results of this study indicate that the role of skills and work abilities in improving product quality consists of four factors, namely; color standards, aroma standards, taste standards, and texture standards. Skills and abilities to process good cake and bread products by creating their own product recipes so that they have unique characteristics accompanied by a more developed garnish presentation model so that they can do their jobs well and satisfactorily. In line with increasing skills coupled with a long work period, pastry staff have qualified experience. In addition, pastry products are starting to show increasingly high quality so that the standards of taste, aroma, texture, and color are increasingly maintained.